2022
DOI: 10.3390/buildings12081283
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Rubble-Stone Masonry Walls Response under Axial Compression Using 2D Particle Modelling

Abstract: To predict the structural behaviour of ancient stone masonry walls is still a challenging task due to their strong heterogeneity. A rubble-stone masonry modeling methodology using a 2D particle model (2D-PM), based on the discrete element method is proposed given its ability to predict crack propagation by taking directly into account the material structure at the grain scale. Rubble-stone (ancient) masonry walls tested experimentally under uniaxial compression loading conditions are numerically evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 22 publications
(43 reference statements)
0
21
0
Order By: Relevance
“…Previous studies conducted by the authors on URM specimens [24,27] have demonstrated that particle models can be effectively utilized as a predictive tool for rubble-stone masonry walls constructed with hydrated air lime mortar [2,10] under uniaxial compressive loading conditions. As demonstrated in [24,27], good agreement can be achieved with stone masonry wall behavior, including elastic response, peak strength, and ductility, provided that the calibration of the contact parameters is based on experimental data of the components obtained from laboratory tests.…”
Section: Modeling Of the Masonry By A Particle Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies conducted by the authors on URM specimens [24,27] have demonstrated that particle models can be effectively utilized as a predictive tool for rubble-stone masonry walls constructed with hydrated air lime mortar [2,10] under uniaxial compressive loading conditions. As demonstrated in [24,27], good agreement can be achieved with stone masonry wall behavior, including elastic response, peak strength, and ductility, provided that the calibration of the contact parameters is based on experimental data of the components obtained from laboratory tests.…”
Section: Modeling Of the Masonry By A Particle Modelmentioning
confidence: 99%
“…In the study presented in [24], three important findings are reported: (i) the lateral numerical model can reproduce the URM peak strength and overall mechanical behavior; (ii) a coarser mortar discretization can be employed without affecting the quality of the numerical predictions; and (iii) a maximum contact compressive yielding stress is necessary to adopt under compression due to the heterogeneity of URM. These findings are encouraging for the use of the 2D-PM model in evaluating the efficacy of transverse reinforcement strengthening systems.…”
Section: Modeling Of the Masonry By A Particle Modelmentioning
confidence: 99%
See 3 more Smart Citations